2015
DOI: 10.1155/2015/847152
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Microcirculatory Blood Flow with a New Sublingual Tonometer in a Porcine Model of Hemorrhagic Shock

Abstract: Tissue capnometry may be suitable for the indirect evaluation of regional hypoperfusion. We tested the performance of a new sublingual capillary tonometer in experimental hemorrhage. Thirty-six anesthetized, ventilated mini pigs were divided into sham-operated (n = 9) and shock groups (n = 27). Hemorrhagic shock was induced by reducing mean arterial pressure (MAP) to 40 mmHg for 60 min, after which fluid resuscitation started aiming to increase MAP to 75% of the baseline value (60–180 min). Sublingual carbon-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…The microcirculation of the sublingual area is frequently investigated, as it is considered a suitable GI region for non-invasive approaches, assuming that the changes might indicate the condition of the microcirculation in more distal sections, such as the ileum. Indeed, earlier studies demonstrated that tissue carbon dioxide pressure in the sublingual area is tied to changes in the small intestinal microcirculation in a hemorrhagic shock and fluid resuscitation model (22). In the present study, we could not detect a correlation between the sublingual microcirculation and the serosal or mucosal components of ileal microperfusion in the resuscitation phase, and this finding highlights the difference between the two methods.…”
Section: Discussioncontrasting
confidence: 71%
“…The microcirculation of the sublingual area is frequently investigated, as it is considered a suitable GI region for non-invasive approaches, assuming that the changes might indicate the condition of the microcirculation in more distal sections, such as the ileum. Indeed, earlier studies demonstrated that tissue carbon dioxide pressure in the sublingual area is tied to changes in the small intestinal microcirculation in a hemorrhagic shock and fluid resuscitation model (22). In the present study, we could not detect a correlation between the sublingual microcirculation and the serosal or mucosal components of ileal microperfusion in the resuscitation phase, and this finding highlights the difference between the two methods.…”
Section: Discussioncontrasting
confidence: 71%
“…Similar findings have been reported, using sublingual capnometric monitoring during bleeding, in both human and animal studies [6,7]. The results of a haemorrhagic shock model in pigs, when complex hemodynamic and blood gas measurements were performed in addition to sublingual capnometry and orthogonal polarisation spectral imaging (OPS) during severe bleeding, were recently detailed [8]. The results suggest that, sublingual to arterial PCO 2 gap values, correlated well with microcirculatory parameters gained by videomicroscopy, and the combination of capnometric monitoring with arterial and central venous blood gas parameters may improve the diagnostic accuracy of haemodynamically relevant haemorrhage or other types of hypoperfusion.…”
Section: Introductionsupporting
confidence: 76%
“…The measurement of the partial pressure of carbon dioxide (pCO 2 ) in tissues is a potentially feasible method for the indirect evaluation of microcirculation [109,110]. Tonometry utilizes the principle that at equilibrium the partial pressure of a diffusible gas such as CO 2 is equal in the mucosa and in the lumen of a viscus.…”
Section: Tissue Capnometrymentioning
confidence: 99%
“…The difference between pCO 2 in the sublingual mucosa and arterial pCO 2 is considered to be predictive of mortality in acute circulatory failure, especially with a cutoff level of 70 mmHg [112,125]. Moreover, the sublingual area is easier to access and free of some limitations of gastric tonometry, such as potential interference of gastric acid [110,126]. The benefits of sublingual capnometry for the management of critically ill or severely injured patients were studied for decades with promising results [12,125,[127][128][129][130][131]; however, its clinical use did not become widespread [112].…”
Section: Tissue Capnometrymentioning
confidence: 99%